Epsin Nanotherapy Regulates Cholesterol Transport to Fortify Atheroma Regression. Issue 1 (6th January 2023) - Cui, Kui; Gao, Xinlei; Wang, Beibei; Wu, Hao; Arulsamy, Kulandaisamy; Dong, Yunzhou; Xiao, Yuling; Jiang, Xingya; Malovichko, Marina V.; Li, Kathryn; Peng, Qianman; Lu, Yao Wei; et al.
Abstract : Background: Excess cholesterol accumulation in lesional macrophages elicits complex responses in atherosclerosis. Epsins, a family of endocytic adaptors, fuel the progression of atherosclerosis; however, the underlying mechanism and therapeutic potential of targeting Epsins remains unknown. In this study, we determined the role of Epsins in macrophage-mediated metabolic regulation. We then developed an innovative method to therapeutically target macrophage Epsins with specially designed S2P-conjugated lipid nanoparticles, which encapsulate small-interfering RNAs to suppress Epsins. Methods: We used single-cell RNA sequencing with our newly developed algorithm MEBOCOST (Metabolite-mediated Cell Communication Modeling by Single Cell Transcriptome) to study cell-cell communications mediated by metabolites from sender cells and sensor proteins on receiver cells. Biomedical, cellular, and molecular approaches were utilized to investigate the role of macrophage Epsins in regulating lipid metabolism and transport. We performed this study using myeloid-specific Epsin double knockout (LysM-DKO) mice and mice with a genetic reduction of ABCG1 (ATP-binding cassette subfamily G member 1; LysM-DKO-ABCG1 fl/+ ). The nanoparticles targeting lesional macrophages were developed to encapsulate interfering RNAs to treat atherosclerosis. Results: We revealed that Epsins regulate lipid metabolism and transport in atherosclerotic macrophages. Inhibiting Epsins by nanotherapy halts inflammation and accelerates atheroma resolution. Harnessing lesional macrophage-specific nanoparticle delivery of Epsin small-interfering RNAs, we showed that silencing of macrophage Epsins diminished atherosclerotic plaque size and promoted plaque regression. Mechanistically, we demonstrated that Epsins bound to CD36 to facilitate lipid uptake by enhancing CD36 endocytosis and recycling. Conversely, Epsins promoted ABCG1 degradation via lysosomes and hampered ABCG1-mediated cholesterol efflux and reverse cholesterol transport. In a LysM-DKO-ABCG1 fl/+ mouse model, enhanced cholesterol efflux and reverse transport due to Epsin deficiency was suppressed by the reduction of ABCG1. Conclusions: Our findings suggest that targeting Epsins in lesional macrophages may offer therapeutic benefits for advanced atherosclerosis by reducing CD36-mediated lipid uptake and increasing ABCG1-mediated cholesterol efflux.